Insecta Diversity on Peudawa Coast, East Aceh District - Samsul Fajri; Sri Jayanthi; Khairunnisa Khairunnisa; Arini Shinta Zahara; Mardiah Mardiah (Jurnal Biologi Tropis, 2023)
Peudawa Beach is one of the beaches in East Aceh or more precisely East Aceh Regency. Insects are  part of the coastal ecosystem. Insects are found in almost all ecosystems. Information on the insect diversity of the banks of Peudawa  has not been thoroughly studied. The purpose of this study is to see the diversity of insect species in Peudawa beach. The method used in this study is an exploratory descriptive research method. In this study, three techniques are used in data collection  technique, namely well drop technique, insect net technique and manual sorting technique. The Shannon-Wiever diversity index (Hand#039;) is used in the data analysis technique. The results of this study show that the insect diversity of Peudawa coast, East Aceh District belongs to the moderate diversity index category, which is influenced by the physical factors of the surrounding environment. The result was 22 insect species in 3 research  stations.